Going to school in World of Warcraft. Observations from a trial programme using off-the-shelf computer games as learning tools in secondary education - Mats Wiklund; Love Ekenberg (Stockholm University Press, 2009)
The use of commercial, off-the-shelf computer games as teaching tools is an interesting possibility, but one that may alter the teacher's role. Unlike specially adapted, game-like educational software, students' attitudes toward the learning potential of computer games may be very different in the presence or absence of an accompanying teacher. The purpose of this work is to investigate whether commercial, unmodified computer games have potential as a tool for learning enhancement, whether varying properties of game genres have an impact on study results, and how the students perceive the teachers role in a learning environment using computer games. Twenty-one students, all of them participants in a longer-term trial programme in game-based education, were interviewed concerning their perceptions of the learning environment, their preferred game genres, and the outcome of their studies. Our findings show that this form of learning results in significantly increased knowledge. It also appears that accompanying teacher activities are important, especially when successfully linked to in-game activities.